THE APPLICATION OF P/Z METHODS IN EVALUATION OF INITIAL GAS IN PLACE OF X RESERVOIRA - lisa samura; Mulia Ginting; Aqlyna Fattahanisa (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2021)
Reservoir X is located in West Tanjung Jabung Regency, Jambi, Indonesia, with initial pressure is 2,028 psia, and a temperature is 226°F. The reservoir has been produced from February 2018 to the present (February 2021), with cumulative gas production of 5.17 Bscf. Based on the Plan Of Development (POD) study in 2016, the initial gas in place was determined volumetrically to be 49,92 Bscf. To compare the initial gas in place, it is deemed necessary to recalculate the initial gas in place by utilizing another method. The calculation of Initial Gas In Place (IGIP) is conducted by using the P/Z method. In this method, the Initial Gas in Place is obtained 49.01 Bscf. Based on analyzing the phase diagrams and the prevailing reservoir conditions, reservoir X indicated a dry gas reservoir. Such reservoir drive mechanism is a depletion drive, determined from the P/Z vs Gp plot, generating a straight line. Based on the assumed abandonment pressure value of 300 psia, the estimated ultimate recovery value is 41.93 Bscf, with the recovery factor value of 87.65% and the remaining reserves of 36.76 Bscf.